Clinical profile of mortality predictors in Leptospirosis:a prospective study in a tertiary care center - Arun Divakar; M. Gopala Krishna Pillai; Elizabeth Thomas (International Journal of Medical Research and Review, 2017)
Aims and Objectives: To look for mortality predictors of Leptospirosis, with specific importance given to oli-guric renal failure and hypotension as possible predictors.Materials and Methods: A Prospective Cohort study conducted over two years which enrolled patients with clinically and serologically confirmed Leptospirosis. Of these, 30 patients were included who had hypotension and 30 patients who had oliguric renal failure, as per statistical requirements. Epidemiological, clinical, and laboratory data was collected at admission and the patients were followed up to look for outcome (discharge/death).Results: A total of 83 patients were included in this study. Of these 8 patients died (Mortality of 9.6%). Data analysis with Chi Square Test showed that oliguric renal failure was significantly associated with mortality in Leptospirosis (p<0.05). Other factors were also found which were associated with mortality including elevated bilirubin and AST levels, anemia, Type 2 Diabetes Mellitus, Alcohol Dependence Syndrome, and Chronic Liver Disease. However, hypotension was found to not be significantly associated with mortality.Conclusion: In patients with Leptospirosis, significant mortality pre-dictors included oliguric renal failure, elevated bilirubin and AST levels, anemia, Type 2 Diabetes Mellitus, Alcohol Dependence Syndrome, and Chronic Liver Disease.